The epichoric writing systems of the Iberian peninsula (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The epichoric scripts of the Iberian Peninsula can be grouped by their internal characteristics in two large groups: the northern scripts, almost completely deciphered, and the southern ones, which still have many signs without consensus values. The first group is made up of the north-eastern Iberian script, with dual standard, dual extended and non-dual variants, and of the Celtiberian script, with eastern and western variants, and each of them in turn with dual and non-dual variants. The second group basically includes the south-eastern Iberian script, apparently always dual, and the south-western script, clearly non-dual. However, everything points to the existence of other southern scripts still to be categorized. Among them are The Espanca script and a small group, located mainly in the Guadalquivir Valley that have common characteristics and that we are already beginning to identify under the denomination of Turdetanian. Both families share a common ancestor, which would probably stem from the Phoenician alphabet, and that would justify the common characteristics of the two families: a similar corpus of signs, the coexistence of alphabetical and syllabic signs and the use of dualities to represent similar sounds by means of adding marks to the same base sign.
Keywords: Palaeohispanic scripts; Palaeohispanic inscriptions; Iberian script; Celtiberian script; Southwestern script; Abecedaries; Script genealogy